2014
DOI: 10.17475/kuofd.87880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weathering on Some Physical Properties of Wood

Abstract: Effects of Weathering on SomePhysicalProperties of Wood AbstractThis study has been held with the aim of determining changes in the hardness, gloss and color of Scotch Pine (PinussylvestrisL.), Eastern Beech (FagusorientalisL.), sessile oak (Quercuspetraea L.) and Anatolian Chestnut (Castanea sativa Mill.) woods which have been exposed to weathering conditions. For this reason, samples have been exposed to weathering conditions for 12 months by essentially taking ASTM D-1641 into consideration and changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
5
0
6
Order By: Relevance
“…This means that the colours in this group of samples became redder after weathering (Figure ). Budakci and Karamanoglu found that natural beech wood gives redder colour values with weathering owing to its characteristic physical properties. The highest positive change to red colour (+Δ a *) was identified in the control and the Tanalith‐E‐impregnated samples, with no statistical difference found between them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the colours in this group of samples became redder after weathering (Figure ). Budakci and Karamanoglu found that natural beech wood gives redder colour values with weathering owing to its characteristic physical properties. The highest positive change to red colour (+Δ a *) was identified in the control and the Tanalith‐E‐impregnated samples, with no statistical difference found between them.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the DL* value increased with tannin impregnation after weathering [21]. Budakci and Karamanoglu [23] found that natural beech wood gives redder colour values with weathering owing to its characteristic physical properties. No significant difference was found between varnish types in terms of DL*.…”
Section: Colour Changesmentioning
confidence: 96%
“…In another study, Scots pine, eastern beech, sessile oak, and chestnut woods were subjected to natural aging. It was reported that the highest gloss change occurred in Scots pine samples (Budakçı and Karamanoğlu 2014).…”
Section: Glossmentioning
confidence: 93%
“…This decrease is thought to be caused by the aging conditions and the physical and chemical factors that occur on the surface after the paint removal process. It is emphasized in the literature that the outdoor conditions have a decreasing effect on the hardness values of the wood material (Yalınkılıç et al 1999;Budakçı and Atar 2001;Baysal 2008;Budakçı and Karamanoğlu 2014;Küçüktüvek et al 2017).…”
Section: Hardnessmentioning
confidence: 99%
“…Weathering decelerates or inverts the spacing and condition of discontinuities from moderately to highly weathered due to cementation processes in discontinuities. Orgunsola et al [5] studied that rock strength decreases as water content increases due to a decrease in the coefficient of internal friction of the rock particles. Additionally, the presence of water in rock increases its deformability.…”
Section: Introductionmentioning
confidence: 99%